Atypical Chronic Myelogenous Leukemia, BCR-ABL1 Negative: Diagnostic Criteria and Treatment Approaches - Diamantopoulos, Panagiotis T.; Viniou, Nora-Athina (Frontiers in Oncology, 2021)
Atypical chronic myelogenous leukemia (aCML) is a rare BCR/ABL1 negative myelodysplastic/myeloproliferative neoplasm, usually manifested with hyperleukocytosis without monocytosis or basophilia, organomegaly, and marked dysgranulopoiesis. In this review, we will discuss the classification and diagnostic criteria of aCML, as these have been formulated during the past 30 years, with a focus on the recent advances in the molecular characterization of the disease. Although this entity does not have a definitive molecular profile, its molecular characterization has contributed to a better understanding and more accurate classification and diagnosis of aCML. At the same time, it has facilitated the identification of adverse prognostic factors and the stratification of patients according to their risk for leukemic transformation. What is more, the molecular characterization of the disease has expanded our therapeutic choices, thoroughly presented and analyzed in this review article.